2008
DOI: 10.1093/molbev/msn059
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Genomics of Host Adaptation in Vesicular Stomatitis Virus

Abstract: Populations experiencing similar selection pressures can sometimes diverge in the genetic architectures underlying evolved complex traits. We used RNA virus populations of large size and high mutation rate to study the impact of historical environment on genome evolution, thus increasing our ability to detect repeatable patterns in the evolution of genetic architecture. Experimental vesicular stomatitis virus populations were evolved on HeLa cells, on MDCK cells, or on alternating hosts. Turner and Elena (2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
136
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(154 citation statements)
references
References 22 publications
13
136
4
1
Order By: Relevance
“…5). All three substitutions have appeared in additional independent experiments during MARM U and/or wt adaptation (4,27,36). These results are consistent with previous work that demonstrated that viruses evolving under regimens of strict positive selection do not necessarily accumulate an excess of nonsynonymous mutations (31).…”
Section: Vol 84 2010 Viral Adaptability and Genomic Evolution 4963supporting
confidence: 89%
“…5). All three substitutions have appeared in additional independent experiments during MARM U and/or wt adaptation (4,27,36). These results are consistent with previous work that demonstrated that viruses evolving under regimens of strict positive selection do not necessarily accumulate an excess of nonsynonymous mutations (31).…”
Section: Vol 84 2010 Viral Adaptability and Genomic Evolution 4963supporting
confidence: 89%
“…Not all potential hosts in the host range (different species or different genotypes of the same species) of a virus are equally susceptible to infection, and it is generally assumed that a tight match may exist between host genotypes and virus genotypes to allow a virus to successfully infect a host (6). Indeed, a substantial amount of data supports the idea that by evolving in a single host species or genotype, viruses become specialists (7)(8)(9)(10), whereas by evolving in multiple host species, the result may be no-cost generalists (7,(11)(12)(13).…”
Section: Importancementioning
confidence: 99%
“…Resource generalization is often assumed to be costly, fostering arguments that natural species biodiversity can be explained by a tendency for niche specialists to be favored over niche generalists (Finke and Snyder 2008). However, many experimental evolution studies in microbes such as RNA viruses have shown that genotypes that evolve to use multiple hosts are not necessarily fitness disadvantaged relative to their more specialized counterparts (Novella et al 1999;Turner and Elena 2000;Remold et al 2008). These collections of microbes could be harnessed to conduct studies examining whether an evolved broad host range is superior to a narrow host range, when avoidance of extinction is the selective challenge.…”
Section: Discussionmentioning
confidence: 99%